It's all about the timing - teaching equestrian feel in practice - Byström, Anna; Lundesjö Kvart, Susanne (Swedish University of Agricultural Sciences, 2025)
Instructing riders is a complex task. The riding teacher needs to pay attention to both horse and rider, give
instructions, and structure the lesson. The aim of this project was to investigate riding teachers’ instructions of transitions. The study included five riders and two teachers in Sweden and in Norway, two lessons per rider (40 in total). Riding teachers were interviewed regarding their teaching, and riders regarding their understanding of the instructions and the horse’s movements. Lessons were video recorded and qualitative analysis was combined with measurements of horse and rider movements and rein tension. It was found that riding teachers have influence on the movement pattern of the horses and riders, as well as rein tension levels. Further, the results highlight the importance of lesson planning to optimise communication between horse and rider. Reflection and feedback on the effects of different choices could be supportive to riding teacher’s professional development.

Att instruera ryttare är komplext eftersom ridläraren samtidigt måste vara uppmärksam på både häst och ryttare, instruera och strukturera lektionen. Syftet med projektet var att studera hur ridlärare instruerar ryttaren under övergångar. Studien inkluderade tio ryttare, fem i Sverige och fem i Norge, som red två hästar var för två olika ridlärare (40 lektioner). Ridlärarna intervjuades om sin undervisning, och ryttarna om sin förståelse av instruktionerna samt hur de uppfattade hästarnas rörelser. Lektionerna videofilmades, och kvalitativ analys kombinerades med objektiv mätning av hästens och ryttarens rörelsemönster samt tygelspänning. Resultaten visar på systematiska skillnader i hästarnas och ryttarnas rörelsemönster och nivå av tygelspänning mellan ridlärare. Det tyder på att lektionsplanering kan påverka kommunikationen mellan häst och ryttare. Ökad reflektion och feedback på hur olika lektionsupplägg påverkar häst och ryttare kan stärka ridlärares kompetensutveckling.
Ryttarkänsla i praktiken - hur man undervisar ryttare
Keywords: biomechanics; biomekanik; teaching and instruction; undervisning; horse sports; hästsport; Sport and Fitness Sciences; Idrottsvetenskap och fitness; Educational Work; Pedagogiskt arbete; Other Social Sciences not elsewhere specified; Övrig annan samhällsvetenskap; Other Veterinary Science; Annan veterinärmedicin